Comparison of Osteoimmunological and Microbiological Parameters of Extra Short and Longer Implants Loaded in the Posterior Mandible: A Split Mouth Randomized Clinical Study - Bilge Karci; Elif Oncu (University of Zagreb. School of Dental Medicine, 2021)
Objectives: This study aimed to evaluate the levels of TNF-α, PGE2, RANKL, RANK, OPG, the markers of periimplant bone loss in peri-implant crevicular fluid obtained around standard and extra short implants. Moreover, the levels of putative oral pathogens were investigated in the submucosal biofilm samples. Material and Methods: The implants were divided into two groups according to their lengths: standard (≥8 mm) and extra short (4 mm). A total of 60 implants were researched in 30 patients. The probing depth (PD), clinical attachment level (CAL), presence of bleeding on probing (BOP), 3-year survival rate (CSR), and bone loss (BL) were measured. Results: No statistically significant difference was found in the values of PD, CAL, BOP, CSR, and BL between the groups (P> 0.05). Total amounts of PGE2, TNF-α, RANKL, RANK, OPG, and RANKL/OPG were not statistically significantly different between the groups (P> 0.05). The abundance of F. nucleatum, T. forsythia, P. intermedia, P. gingivalis, S. oralis and T. denticola was compared between the groups and the results were not statistically significant (P> 0.05). Conclusion: The results of this study suggested that PGE2, TNF-α, RANKL, RANK, OPG, and RANKL/OPG in PICF, as well as microbiological parameters in submucosal biofilms, were similar between standard (≥8 mm) and extra short (4 mm) implants. Therefore, the implant length does not seem to influence the bone loss, levels of osteoimmunological and microbiological markers in the peri-implant tissues and survival rates.